Heat and mass transfer in drying of porous media - Xu, Peng, 1973-; Sasmito, Agus P.; Mujumdar, Arun S. (Boca Raton, FL : CRC Press, Taylor & Francis, 2020)
Heat and Mass Transfer in Drying of Porous Media offers a comprehensive review of heat and mass transfer phenomena and mechanisms in drying of porous materials. It covers pore-scale and macro-scale models, includes various drying technologies, and discusses the drying dynamics of fibrous porous material, colloidal porous media and size-distributed particle system. Providing guidelines for mathematical modeling and design as well as optimization of drying of porous material, this reference offers useful information for researchers and students as well as engineers in drying technology, food processes, applied energy, mechanical, and chemical engineering.
4.3.2. Freeze Drying4.3.2.1. The Development of a Numerical Simulation of Freeze Drying; 4.3.2.2. The Numerical Simulation of Technological Parameters to Intensify Drying; 4.3.3. Radio Frequency Drying; 4.3.3.1. Numerical Simulation Development of Radio Frequency Heating; 4.3.3.2. Application of Numerical Simulation to Enhance Uniformity Radio Frequency Heating; 4.3.3.3. Numerical Simulation of the Combination of Radio Frequency and Conventional Drying; 4.3.3.4. Numerical Simulation of Radio Frequency/Vacuum Drying; 4.3.4. Spray Drying
4.3.4.1. The Numerical Simulation of Equipment Design for Improving Droplets Movement
OCLC-licensed vendor bibliographic record.
Keywords: Drying; Mass transfer; Heat -- Transmission; SCIENCE / Chemistry / Industrial & Technical; SCIENCE / Mechanics / Dynamics / Thermodynamics; TECHNOLOGY / Engineering / Chemical & Biochemical